OPTIMAL LIGHT INTENSITY AND PHOTOPERIOD FOR THE GROWTH AND QUALITY OF PLATOSTOMA PALUSTRE IN A PLANT FACTORY - Yanfen Huang; Fan Wei; Changqian Quan; Danfeng Tang (Journal of Animal and Plant Sciences, 2024)
Platostoma palustre (Blume) A. J. Paton is an important medicinal and edible plant in China and Southeast Asian countries with great market and economic value. In recent years, due to the high labor cost of cultivation and management of P. palustre and limited economic benefits, domestic farmers have been hesitant to plant it. This has led to an inadequate supply of raw materials for P. palustre in China, necessitating the import of large quantities from Southeast Asian countries. Consequently, alternative methods for planting and cultivating P. palustre beyond traditional field practices are needed. In this study, a hydroponic experiment was conducted to investigate suitable lighting conditions for P. palustre growth in a plant factory. The experiment involved a two-factor, four-level design incorporating red light intensities of 50, 100, 150, 200 μmol/(m2·s) and photoperiods of 8h/16h, 12h/12h, 16h/8h, 20h/4h Light/Darkness (L/D). The results showed that increasing red light intensity and duration promoted the whole plant weight and stem diameter of P. palustre to some extent, while extending light duration was beneficial for the leaf area. Light intensities ranging from 50 to 150 μmol/(m2·s) combined with a 20h/4h L/D photoperiod favored the accumulation of total chlorophyll, chlorophyll a, chlorophyll b, and carotenoid. Prolonged photoperiods and higher light intensities facilitated the root growth of P. palustre. Light intensitiesbetween 100 and 200 μmol/(m2·s) with an 8h/16h L/D photoperiod were helpful for the accumulation of total pectin and soluble sugar content. Membership function analysis indicated that the T12 treatment (150 μmol/(m2·s) light intensity and 20h/4h L/D photoperiod) was more suitable for the cultivation and quality production of P. palustre in the plant factory. The current study provided scientific data for plant factory or indoor large-scale cultivation and planting of P. palustre.
Keywords: p. palustre; light intensity; photoperiod; growth; quality